Bidirectional Association Between Obsessive-Compulsive Disorder and Systemic Autoimmune Diseases Among Probands and Unaffected Siblings: A Nationwide Population-Based Study. Issue 5 (31st January 2022) - Liou, Ying-Jay; Tsai, Shih-Jen; Bai, Ya-Mei; Cheng, Chih-Ming; Chen, Tzeng-Ji; Liang, Chih-Sung; Chen, Mu-Hong
ABSTRACT: Objective: Studies have reported a biological link between obsessive-compulsive disorder (OCD) and systemic autoimmune disease (SAID). However, whether the unaffected siblings of patients with OCD or SAID are more likely to develop subsequent SAID or OCD later in life remains unclear. Methods: We examined the Taiwan National Health Insurance Research Database data of 17, 135 patients with SAID, 30, 672 unaffected siblings, and 467, 211 non-SAID reference subjects born before 2000 for subsequent OCD during 1996–2011 and those of 25, 364 patients with OCD, 42, 546 unaffected siblings, and 654, 207 non-OCD reference subjects to identify subsequent SAID during 1996–2011. Results: Patients with SAID (odds ratio = 1.74, 95% confidence interval = 1.31–2.31) and unaffected siblings (1.25, 0.92–1.70) were more likely to develop OCD later in life than the non-SAID reference group. Moreover, patients with OCD (odds ratio = 1.53, 95% confidence interval = 1.15–2.05) and unaffected siblings (1.51, 1.21–1.87) were more likely to develop any form of SAID during the follow-up than the non-OCD reference group. Conclusions: The bidirectional association of OCD and SAID between probands and siblings may indicate a familial coaggregation of these two conditions. Additional studies elucidating the genetic and environmental mechanisms underlying this coaggregation are warranted.